2008
DOI: 10.1051/orthodfr:2008006
|View full text |Cite
|
Sign up to set email alerts
|

La déglutition dysfonctionnelle a-t-elle une influence sur la posture ?

Abstract: Swallowing is one of the first functions to be set up in utero for vital reasons. Physiological and psychic maturation then occur to lead from a dysfunctional to a functional state. Nevertheless, for certain individuals, maturation is incomplete, and swallowing remains dysfunctional. The clinical literature has already proven the incidence of a dental change of occlusion and the consequences of a lingual dysfunction upon posture. This work proposes to show that the posture can be affected by dysfunctional degl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is further confirmation, consistent with results of other studies mentioned, that the economy of sensorimotor activation of the tongue in elevation, compared to the greater cortical and subcortical sensorimotor activation in protrusion, is a guiding principle in promoting tongue elevation in patients during therapy as this position or movement is less complicated and less dependent on cognitive skills, in absence of overriding breathing issues that change the overall pattern of tongue posture at rest and during swallow., [44]. Bocquet et al, [78] suggest we might suppose a reduction of motor unit recruitment during tongue elevation task, suggesting a reduction in energy expenditure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is further confirmation, consistent with results of other studies mentioned, that the economy of sensorimotor activation of the tongue in elevation, compared to the greater cortical and subcortical sensorimotor activation in protrusion, is a guiding principle in promoting tongue elevation in patients during therapy as this position or movement is less complicated and less dependent on cognitive skills, in absence of overriding breathing issues that change the overall pattern of tongue posture at rest and during swallow., [44]. Bocquet et al, [78] suggest we might suppose a reduction of motor unit recruitment during tongue elevation task, suggesting a reduction in energy expenditure.…”
Section: Discussionmentioning
confidence: 97%
“…Bocquet et al in 2008 [78] already examined whether dysfunctional swallowing influences postural parameters as well. Those authors found that swallowing would have the same postural effects as cognitive tasks by increasing the postural oscillations and the energy spent by the postural system [78].…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, through the connection with the spine, the head can modify the whole body posture (Shaghayegh Fard et al, 2016;Szczygiel et al, 2019). Since swallowing disorder (SD) is an alteration of the physiological tongue movement that occurs during the act of swallowing, this phenomenon can adversely affect human posture (Begnoni et al, 2019;Bocquet et al, 2008;Machado Junior and Crespo, 2012;Messina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%